Inkulturacija, fenomen kulturnih procesov na KoroškemInculturation, a Phenomenon of Cultural Processes in Carinthia - Schnabl, Bojan Ilija (Studia mythologica Slavica, 2012)
In the perspective of cultural sciences »inculturation« is a phenomenon of transfer of cultural and mythological elements from one culture or religion to the other. Phenomenons of inculturation are known in the transition from paganism to Christianity. Processes of inculturation became relevant within the Iro-Scottisch Mission in Carantania with the use of the Slavic/Carantano-Slovenian language as liturgical language in the Freising Manuscript as well as through the use of the well integrated Slavic/Carantano-Slovenian Christian terminology of Ladinic origin 100 years later within the Cyrillo-Methodian translation of the whole Bible in the Old Church Slavic language. The article is expanded and adapted entry »Inculturation« from the upcoming »Encyclopedia of the Slovenian Language, Literature, and Culture in Carinthia: From the Early Beginnings until 1938« [Enzyklopädie der slowenischen Sprache, Literatur und Kultur in Kärnten/Koroška, von den Anfängen bis 1938], and discusses relevant terminology and cultural elements].